Light bulbs comparison from different brand and working principle - Muhammad Siddiq Fadhil, Sutrisno; Nurulain, S.; Nurzuraini, Omar Sharif; Mohd Rashidi, Salim; Hadi, Manap (Springer Science and Business Media Deutschland GmbH, 2022)
Choosing the best light bulbs for energy saving purpose is common for consumers and mostly will prefer a low power rated bulb. However, some low power rated bulbs are false claimed. Therefore, this paper reports the comparison between light bulbs with different brands in local market. The comparison is carried out in term of light intensity, energy usage, circadian rhythm and price for a few low power rated bulbs. The method used to measure the light intensity was using a spectrometer. The energy usage for all bulbs are measured and eventually the results is tabulated and analyzed. From the experiment, it can be deduced that every light bulb had its own advantages and deficiencies in term of light intensity, energy usage and price. The result also shows that some light bulbs are over rated in term of power usage. The power measured are much higher (88- to 135%) compare to the power rated by the manufacturer. It is hoped that this paper can be used by the consumer as a reference to choose the best bulb for lighting purpose.